2014
DOI: 10.1371/journal.pone.0103816
|View full text |Cite|
|
Sign up to set email alerts
|

Salivary Gland Proteome Analysis Reveals Modulation of Anopheline Unique Proteins in Insensitive Acetylcholinesterase Resistant Anopheles gambiae Mosquitoes

Abstract: Insensitive acetylcholinesterase resistance due to a mutation in the acetylcholinesterase (ace) encoding ace-1 gene confers cross-resistance to organophosphate and carbamate insecticides in Anopheles gambiae populations from Central and West Africa. This mutation is associated with a strong genetic cost revealed through alterations of some life history traits but little is known about the physiological and behavioural changes in insects bearing the ace-1R allele. Comparative analysis of the salivary gland cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Indeed, because mosquitoes develop different resistance mechanisms to carbamates and pyrethroids, the impact of the resistance to one family could be different to what observed for the other. However, the down-regulation of D7 family genes observed in our study is in accordance with results of previous studies after comparative proteomic analysis of expressed proteins in bendiocarb susceptible and resistant mosquitoes [46,47]. Indeed, in these studies conducted in Culex quinquefasciatus [48] and An.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, because mosquitoes develop different resistance mechanisms to carbamates and pyrethroids, the impact of the resistance to one family could be different to what observed for the other. However, the down-regulation of D7 family genes observed in our study is in accordance with results of previous studies after comparative proteomic analysis of expressed proteins in bendiocarb susceptible and resistant mosquitoes [46,47]. Indeed, in these studies conducted in Culex quinquefasciatus [48] and An.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in these studies conducted in Culex quinquefasciatus [48] and An. gambiae [47], the D7 long form (the sole member of D7 family protein detected) presented lower expression in the resistant strain than the susceptible strain. Globally, it appears that the pattern of how insecticide resistance is associated to the differential expression of D7 family genes remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti salivary gland extract enhances dengue pathogenesis after infection [ 16 ]. In previous studies, differential expression of salivary gland proteins between insecticide-susceptible and resistant strains of Culex quinquefasciatus [ 17 ], Anopheles gambiae [ 18 ] and Anopheles stephensi [ 19 ] has been reported. Regarding insecticide resistant mosquitoes in Thailand, no report of differentially expressed salivary gland proteins between susceptible and insecticide-resistant Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, an increasing number of studies have compared differentially expressed proteins in vector mosquitoes, but these refer to proteins from the salivary glands (Cornelie et al , ; Vijay et al , ) or from the whole larval body (Wang et al , ), rather than the midgut. The studies cited above identified proteins that differ from those reported herein.…”
Section: Discussionmentioning
confidence: 99%